Covert infection with an RNA virus affects medfly fitness and the interaction with its natural parasitoid Aganaspis daci - Hernández-Pelegrín, Luis; García-Martínez, Ricardo; Llácer, Elena; Nieves, Lorena; Llopis-Giménez, Ángel; Català-Oltra, Marta; Dembilio, Óscar; Pérez-Hedo, Meritxell; Urbaneja, Alberto; Vera I.D., Ros; Beitia, Francisco J.; Herrero, Salvador (Springer, 2025)
With the advent of high-throughput sequencing, large sets of insect-infecting RNA viruses producing apparent asymptomatic infections are being discovered. In the Mediterranean fruit fy (medfy) Ceratitis capitata, an agricultural key pest of a wide range of fruits, 13 diferent RNA viruses have been described so far. Recent analysis demonstrated a wide distribution of these viruses in diferent medfy strains collected worldwide, but little is known about the interactions between those viruses and the medfy host. Previous studies suggested that a higher abundance of Ceratitis capitata nora virus (CcaNV) correlated with a shorter lifespan in adults. Here, we investigated the efect of CcaNV on a broad range of parameters related to host ftness and its interaction with other trophic levels. CcaNV purifed from a naturally infected medfy strain was added to the larval diet. Pupal weight, adult emergence, fying ability, and longevity were monitored after oral infections. Our results revealed detrimental efects associated with a CcaNV infection in the medfy, in terms of reduced pupal weight and reduced adult longevity. Moreover, we tested the infuence of a CcaNV infection in medfies on the parasitism performance of Aganaspis daci, an endoparasitoid used in biological control programs against medfies. Our results showed that A. daci progeny increased when parasitizing on CcaNV-infected larvae. Overall, we proved that covert RNA viruses can impact the insect ecology, directly afecting its insect host biology and indirectly infuencing multitrophic interactions.